The Hypertension of Hemophilia Is Not Explained by the Usual Cardiovascular Risk Factors: Results of a Cohort Study - Richard F. W. Barnes; Thomas J. Cramer; Afrah S. Sait; Rebecca Kruse-Jarres; Doris V. K. Quon; Annette von Drygalski (International Journal of Hypertension)
Background. The etiology of the high prevalence of hypertension among patients with hemophilia (PWH) remains unknown. Methods. We compared 469 PWH in the United States with males from the National Health and Nutrition Examination Survey (NHANES) to determine whether differences in cardiovascular risk factors can account for the hypertension in hemophilia. Results. Median systolic and diastolic BP were higher in PWH than NHANES (P<0.001) for subjects not taking antihypertensives. Those taking antihypertensives showed similar differences. Differences in both systolic and diastolic BP were especially marked among adults <30 years old. Differences between PWH and NHANES persisted after adjusting for age and risk factors (body mass index, renal function, cholesterol, smoking, diabetes, Hepatitis C, and race). Conclusions. Systolic and diastolic BP are higher in PWH than in the general male population and especially among PWH < 30 years old. The usual cardiovascular risk factors do not account for the etiology of the higher prevalence of hypertension in hemophilia. New investigations into the missing link between hemophilia and hypertension should include age of onset of hypertension and hemophilia-specific morbidities such as the role of inflammatory joint disease.